2018
DOI: 10.1021/acsomega.7b01873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anions on the Partition Constant, Self-Diffusion, Thermal Stability, and Toxicity of Dicationic Ionic Liquids

Abstract: Partition constants (KD°), molecular dynamics (T1, T2, and DOSY measurements), thermal stability, and toxicity of dicationic ionic liquids (ILs) were determined. The dicationic ILs derived from 1,n-bis(3-methylimidazolim-1-yl)octane, [BisOct(MIM)2][2X] (in which X = Cl, Br, NO3, SCN, BF4, and NTf2), were evaluated to verify the influence of anion structure on the IL properties. A monocationic IL [Oct(MIM)][Br] was also monitored for comparison. In general, the solubility of the ILs followed the anion free ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Another crucial aspect of ILs is their potential toxicity, which has been scrutinized during the last 10 years. On this regard, the studies performed up to now showed promising toxicity profiles for DILs when compared with the corresponding monocationic ILs (Pretti et al, 2009; Frizzo et al, 2018; Montalbána et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Another crucial aspect of ILs is their potential toxicity, which has been scrutinized during the last 10 years. On this regard, the studies performed up to now showed promising toxicity profiles for DILs when compared with the corresponding monocationic ILs (Pretti et al, 2009; Frizzo et al, 2018; Montalbána et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…2013; Frizzo et al . 2018). Around 500 C. elegans (L1) were transferred to microtubes containing different mefenoxam and pyraclostrobin concentrations in M9 buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The worms were continuously shaken to stimulate oxygenation. After 1 h, the worms were washed three times with M9 buffer, and the survival assay was then performed [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous, imidazolium-based DILs [C 8 (MIM) 2 ][2X], in which X = Cl, Br, NO 3 , SCN, and BF 4 , and their toxicological effects against C. elegans were reported by us. In our early scanning, increasing concentrations of IL (0.01, 0.1, 1.0, and 10 mM) were added to the first stage of the worms (larval stage), which is more sensitive, and remained for 1 h. Results showed that the survival of above 90% of C. elegans indicated that these ILs do not have toxic effects at the concentrations evaluated [ 19 ].…”
Section: Introductionmentioning
confidence: 99%